Both Adjustable and Fixed Loop Hamstring Tendon Graft Fixation Have Similar Clinical and Patient-Reported Outcomes in Anterior Cruciate Ligament Reconstruction - Christian Hwee Yee Heng, M.B.B.S., F.R.C.S.Ed. (Orth); Joel Yat Seng Wong, M.B.B.S; Andrew Hwee Chye Tan, M.B.B.S., F.R.C.S.Ed. (Orth) (Elsevier, 2023)
Purpose: This study aims to compare the outcomes of fixed-loop device (FLD) vs adjustable-loop device (ALD) graft fixation with up to 2-year follow-up in patients undergoing primary anterior cruciate ligament reconstruction (ACLR) in a predominantly Asian setting. Methods: Prospectively collected outcome measures as well as clinical records of patients who underwent primary ACLR using either FLD or ALD fixation of hamstring tendon autograft performed by a single surgeon were reviewed. The surgeon in this study used a fixed-loop device from 2018 to 2019 and then changed to adjustable loop from 2019 to 2020. Suspensory fixation was performed on the femoral side, and aperture (interference screw) fixation was performed on the tibial side. Outcome measures included knee range of motion, KT-1000 arthrometer testing, Lysholm knee score, and Tegner activity scale. Patients were assessed preoperatively and postoperatively at regular intervals of 6, 12, and 24 months. Results: A total of 105 patients were identified. Forty-six were excluded due to incomplete follow-up data, so 59 patients with full 2-year follow-up were included in the final study group. Both groups (FLD vs ALD) were similar in demographics except for age (P = .042). Out of 105, there were 59 patients remaining in the study group with 2-year follow-up data. No significant differences were observed between the 2 groups at all respective testing intervals. Conclusions: FLDs and ALDs for suspensory fixation of hamstring tendon autograft in ACLR had similar clinical outcomes with a minimum of 2-year follow up. There is no evidence of graft loosening from loop lengthening. Level of Evidence: Level III, retrospective comparative trial.